2006
DOI: 10.1243/13506501jet75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water temperature on the adhesion between rail and wheel

Abstract: The effects of factors such as rolling speed, contact load, water temperature, and surface roughness on the adhesion coefficient between wheel and rail under wet conditions were investigated theoretically by adopting elasto-hydrodynamic lubrication theory and rough surfaces contact theory [1]. It was found that the water temperature and the surface roughness greatly affect the adhesion performance comparing the other factors. This paper describes an experimental investigation on the effect of water temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…The approach taken by nishida et al (1985) differed in using a 6 m diameter circular track on which wheels ran upright. Several mid-scale simulators using scaled down wheels have also been produced (Kalousek et al, 1982;iwnicki and Wickens, 1998;chen et al, 2006), although these have in many cases been focused on rail-wheel dynamics rather than wear and fatigue.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…The approach taken by nishida et al (1985) differed in using a 6 m diameter circular track on which wheels ran upright. Several mid-scale simulators using scaled down wheels have also been produced (Kalousek et al, 1982;iwnicki and Wickens, 1998;chen et al, 2006), although these have in many cases been focused on rail-wheel dynamics rather than wear and fatigue.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Chen et al conducted a number of adhesion tests under the wet condition using a scaled twin‐disc machine. They mainly focused on the effect of surface parameters on the adhesion coefficient . Wang et al had obtained the wheel‐rail adhesion curve under wet condition with different water volume conditions using a subscale wheel/rail configuration .…”
Section: Introductionmentioning
confidence: 99%
“…It can be recognised as the close simulation of different starved conditions. However, laboratory tests mentioned above had been conducted by railway engineers under different contaminations were almost at low or moderate speed conditions . Zhang et al carried out the full‐scaled laboratory adhesion tests with different interfacial conditions on adhesion under high‐speed condition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 It is found that the water temperature has a significant influence on adhesion level of wheel/rail interface and a rise in water temperature causes an increase in the adhesion coefficient. 10 Furthermore, many methods of improving adhesion coefficient have been reported and discussed. [11][12][13][14] Sanding has been a common practice to increase the adhesion coefficient of wheel/rail under the oil and water conditions.…”
Section: Introductionmentioning
confidence: 99%